Integrated Analysis of FAM57A Expression and Its Potential Roles in Hepatocellular Carcinoma - Wei, Junwei; Liu, Yun; Zhao, Caiyan (Frontiers in Oncology, 2021)
Background: Family with sequence similarity 57 member A (FAM57A) is a membrane associated gene contributing to lung carcinogenesis. In hepatocellular carcinoma (HCC) and other cancers, whether FAM57A exerts similar roles has been rarely reported. Herein, the biological functions and clinical significance of FAM57A in HCC were explored. Methods: We first explored and validated FAM57A differential expression between non-tumor and HCC tissues using a number of public databases and immunohistochemistry (IHC), respectively. Then, the Kruskal-Wallis rank sum test or the Wilcoxon rank sum test as well as logistic regression were employed to analyzed the association of FAM57A expression with clinical characteristics of HCC. The Cox regression and Kaplan-Meier analyses were conducted to assess the prognostic significance. Moreover, with the co-expression analysis, Gene Ontology (GO), Gene Set Enrichment Analysis (GSEA), and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis, the molecular pathomechanisms that are mediated by FAM57A in HCC were elucidated. Finally, In vitro cell functional assay was carried out to preliminarily verify the role of FAM57A in HCC. Results: FAM57A was higher in HCC samples than in non-tumor samples (all p-value <0.05). FAM57A expression was positively associated with clinicopathological characteristics (clinical stage, T stage, pathological grade) and negatively linked to the HCC patients’ survival. Univariate and multivariate Cox regression analyses uncovered that FAM57A expression could independently predict prognosis in HCC patients. Functional enrichment analyses further indicated that FAM57A was involved in multiple pathways related to tumors. Functional assay revealed that FAM57A knockdown significantly decreased the proliferative abilities of HCC cells. Conclusions: Our results indicated that FAM57A might function as an oncogene to promote HCC progression and could predict clinical course of HCC.